MdBZR1 and MdBZR1-2like Transcription Factors Improves Salt Tolerance by Regulating Gibberellin Biosynthesis in Apple - Wang, Xuxu; Chen, Xiude; Wang, Qingjie; Chen, Min; Liu, Xiao; Gao, Dongsheng; Li, Dongmei; Li, Ling (Frontiers in Plant Science, 2019)
Brassinosteroids (BRs) are a group of plant steroid hormones that play important roles in regulating plant development. In addition, BRs show considerable functional redundancy with other plant hormones such as gibberellins (GAs). BRASSINAZOLE RESISTANT1 (BZR1) and BRI1-EMS-SUPPRESSOR1 (BES1) transcription factors are negative feedback regulators of BR biosynthesis. This study provides evidence for the roles of MdBZR1 and MdBZR1-2like in promoting GA production. This results also show that BRs regulate GA biosynthesis to improve salt tolerance in apple calli. Moreover, this research proposes a regulatory model, in which MdBZR1 and MdBZR1-2like bind to the promoters of GA biosynthetic genes to regulate their expression in a BR-dependent manner. The expression of key GA biosynthetic genes, MdGA20ox1, MdGA20ox2, and MdGA3ox1 in yeast helps to maintain normal growth even under intense salt stress. In summary, this study underscores the roles of MdBZR1 and MdBZR1-2like in improving salt tolerance by regulating gibberellin biosynthesis in apple calli.